Public Value Layanan Kredit Serba Guna Bank Sumsel Babel Cabang Prabumulih dalam Meningkatkan Inklusi Keuangan Bagi Aparatur Sipil Negara di Kota Prabumulih - Salsabila Putri Maharani M; Annada Nasyaya (Public Service and Governance Journal, 2026)
This study aims to analyze the creation of public value through the Multi-Purpose Credit (KSG) program implemented by Bank Sumsel Babel Prabumulih Branch in improving financial inclusion for civil servants (ASN) in Prabumulih City. The analysis employs Mark H. Moore's Public Value Strategic Triangle, which consists of three core dimensions: public value, legitimacy and support, and operational capacity. Using a qualitative descriptive method, data were obtained through in-depth interviews, field observations, and document analysis involving seven informants, including internal bank officials and KSG borrowers with varying credit statuses (current, substandard, and non-performing). Overall, the study concludes that the KSG program successfully creates public value by expanding access to formal financial services, strengthening ASN financial literacy, and contributing to local financial inclusion. The findings indicate that the program not only functions as a banking product but also as a public service instrument that supports socioeconomic stability among civil servants. However, several challenges remain, particularly in ensuring equal benefits for borrowers facing repayment difficulties. Therefore, improvements in post-disbursement support, the development of online consultation services, and the provision of continuous and targeted financial education are needed to enhance program sustainability and ensure that public value is distributed more evenly among all borrower categories.